Adverse neonatal outcomes and associated factors among mothers who gave birth through induced and spontaneous labor in public hospitals of Awi zone, Northwest Ethiopia: a comparative cross-sectional study - Melaku Laikemariam; Almaz Aklilu; Fikadu Waltengus; Melkamu Addis; Wubishet Gezimu; Fekadu Baye; Temesgen Getaneh (BMC, 2023)
Abstract Background Adverse neonatal outcomes are one of the most common causes of neonatal mortality and morbidity. Empirical evidence across the world shows that induction of labor potentiates adverse neonatal outcomes. In Ethiopia, there has been limited data that compares the frequency of adverse neonatal outcomes between induced and spontaneous labor. Objectives To compare the prevalence of adverse neonatal outcomes between induced and spontaneous labor and to determine associated factors among women who gave birth in public hospitals of Awi Zone, Northwest Ethiopia. Methods A comparative cross-sectional study was conducted at Awi Zone public hospitals from May 1 to June 30, 2022. A simple random sampling technique was employed to select 788 (260 induced and 528 spontaneous) women. The collected data were analyzed using statistical package for social science (SPSS) software version 26. The Chi-square test and an independent t-test were used for categorical and continuous variables, respectively. A binary logistic regression was used to assess the association between the outcome and explanatory variables. In the bivariate analysis, a p-value ≤ 0.2 at a 95% confidence interval was used to consider the variables in the multivariate analysis. Finally, statistical significance was stated at a p-value of less than 0.05. Result The adverse neonatal outcomes among women who gave birth through induced labor were 41.1%, whereas spontaneous labor was 10.3%. The odds of adverse neonatal outcomes in induced labor were nearly two times higher than in spontaneous labor (AOR = 1.89, 95% CI: 1.11-3.22). No education (AOR = 2.00, 95% CI: 1.56, 6.44), chronic disease (AOR = 3.99, 95% CI: 1.87, 8.52), male involvement (AOR = 2.23, 95% CI: 1.23, 4.06), preterm birth (AOR = 9.83, 95% CI: 8.74, 76.37), operative delivery (AOR = 8.60, 95% CI: 4.63, 15.90), cesarean section (AOR = 4.17, 95% CI: 1.94, 8.95), and labor complications (AOR = 5.16, 95% CI: 2.90, 9.18) were significantly associated factors with adverse neonatal outcomes. Conclusion and recommendation Adverse neonatal outcomes in the study area were higher. Composite adverse neonatal outcomes were significantly higher in induced labor compared to spontaneous labor. Therefore, it is important to anticipate the possible adverse neonatal outcomes and plan management strategies while conducting every labor induction.